2004
DOI: 10.1111/j.0031-9317.2004.00302.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification, cloning and expression analysis of strawberry (Fragaria × ananassa) mitochondrial citrate synthase and mitochondrial malate dehydrogenase

Abstract: Salt-extractable proteins from the cell walls of immature and ripe strawberry (Fragaria x ananassa Duch. cv. Elsanta) fruit were separated using two-dimensional polyacrylamide gel electrophoresis. Seven polypeptides (enzymes) were characterized from their N-terminal sequences: (1) glyceraldhyde-3-phosphate dehydrogenase (EC 1.2.1.12); (2) triose phosphate isomerase (TPI; EC 5.3.1.1); (3) mitochondrial malate dehydrogenase (mMDH; EC 1.1.1.37); (4) NADH glutamate dehydrogenase (EC 1.4.1.3); (5) chalcone synthase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 62 publications
2
16
1
Order By: Relevance
“…The resonance arising due to citrate was first observed at stage IV and increased sharply until maturity of the fruits. Similar increase in the levels of citrate and malate has been reported in developing fruits of strawberry (Iannetta et al, 2004).…”
Section: Metabolic Analysis Of Polar Extractssupporting
confidence: 84%
“…The resonance arising due to citrate was first observed at stage IV and increased sharply until maturity of the fruits. Similar increase in the levels of citrate and malate has been reported in developing fruits of strawberry (Iannetta et al, 2004).…”
Section: Metabolic Analysis Of Polar Extractssupporting
confidence: 84%
“…With either of these approaches, there is a risk that the measurements collated do not reflect the ripening processes that occur in planta. This may be due to the removal of important growth promoters as a result of fruit detachment and/or dissection or due to the release of components in fruit extracts that inhibit enzyme activities or bind protein or metabolites (Iannetta et al 2004, Souleyre et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…NAD-MDH is the key enzyme of malic acid production in fruits. Iannetta et al (2004) found that NAD-MDH activity was greatly enhanced with increasing malic acid content as strawberries mature. Our study suggested that the NAD-MDH activity in the apples on the No.…”
Section: Discussionmentioning
confidence: 95%